1980
DOI: 10.1172/jci109875
|View full text |Cite
|
Sign up to set email alerts
|

Variable Thyrotropin Response to Thyrotropin-releasing Hormone after Small Decreases in Plasma Free Thyroid Hormone Concentrations in Patients with Nonthyroidal Diseases

Abstract: A B S T R A C T Although a normal serum thyrotropin (TSH)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

1981
1981
2009
2009

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(12 citation statements)
references
References 29 publications
(43 reference statements)
0
12
0
Order By: Relevance
“…The pathogenetic mechanism remains to be elucidated. A possible cause could be the presence of functional central hypothyroidism in severe NTI (5,13,14). This could lead to understimulation of the thyroid gland resulting in involutional changes as described above.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenetic mechanism remains to be elucidated. A possible cause could be the presence of functional central hypothyroidism in severe NTI (5,13,14). This could lead to understimulation of the thyroid gland resulting in involutional changes as described above.…”
Section: Discussionmentioning
confidence: 99%
“…Further more, patients with chronic renal failure have been known to exhibit a blunted and delayed TSH response to TRH [13]. Maturlo et al [22] have examined this relationship in considerable detail in NTI patients. Their studies showed an inappropriate response of TSH to TRH in about one half of systematically ill patients treated with iodide to affect decrements in serum TT4 and TT3.…”
Section: Discussionmentioning
confidence: 99%
“…Increased serum levels of interleukin-6 have been observed in b-thalassemia (T Alexandrides, P Matsuka & A Vagenakis, unpublished observations). However, patients with the euthyroid sick syndrome are not susceptible to the inhibitory effects of iodide despite the fact that serum cytokines are increased in the majority of these patients (28,29).…”
Section: Discussionmentioning
confidence: 99%